2022
DOI: 10.3389/fcvm.2022.954704
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged dual antiplatelet therapy after drug-eluting stent implantation in patients with diabetes mellitus: A nationwide retrospective cohort study

Abstract: BackgroundOptimal duration of dual antiplatelet therapy (DAPT) in patients with diabetes mellitus (DM) who have undergone drug-eluting stent (DES) implantation is not clearly established. This study sought to impact of DAPT duration on real-world clinical outcome in patients with or without DM.MethodsUsing a nationwide cohort database, we investigate the association between DAPT duration and clinical outcome between 1 and 3 years after percutaneous coronary intervention (PCI). Primary outcome was all-cause dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…DM has always been an independent risk factor for adverse cardiovascular outcomes following PCI. Previous studies have shown DM to be an independent risk factor for the development of adverse cardiovascular outcomes whether with or without insulin therapy [ 21 ], whether with different coronary stents [ 22 ] or with prolonged duration of DAPT [ 23 ]. Studies have also shown that the longer the duration of DM, the higher the major adverse cardiovascular events observed after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…DM has always been an independent risk factor for adverse cardiovascular outcomes following PCI. Previous studies have shown DM to be an independent risk factor for the development of adverse cardiovascular outcomes whether with or without insulin therapy [ 21 ], whether with different coronary stents [ 22 ] or with prolonged duration of DAPT [ 23 ]. Studies have also shown that the longer the duration of DM, the higher the major adverse cardiovascular events observed after PCI.…”
Section: Discussionmentioning
confidence: 99%